Numerical simulation of low reynolds number 2-d rough blade compressor cascade - Wang, Li-Song; Wang, Zhong-Yi; Wang, Yan-Hua; Wang, Meng; Sun, Hai-Ou (Frontiers in Energy Research, 2022)
In this paper, a double-circular-arc cascade was used as the research object to study the effect of roughness on the compressor cascade under the conditions of different incoming attack angles. The Reynolds number of the cascade is 1.5×105 . The profile of the suction surface is changed to simulate the change in surface roughness. A uniformly distributed 238 control points were selected on the suction surface profile of the smooth blade. The 238 points are increased randomly along with the normal phase of the wall, and a smooth curve connects these points to obtain a rough suction surface profile. In this study, numerical simulation methods were used to calculate the cascade flow field under 5 kinds of attack angles and 6 kinds of suction surface roughness (including smooth surface). In this paper, k−ω SST and large eddy simulation were used for numerical simulation calculation with the model respectively. The calculation results show that the effect of roughness on the flow field of the cascade is different under different angles of attack. When 70<ks+<130 the rough suction surface can increase the lift coefficient of the compressor blade.